Planning Management of Takhaṣṣuṣ al-Lughah al-ʿArabiyah Program at The Al-Kamal Integrated Islamic Boarding School Blitar - Achmad Sirojul Munir (Alsuna: Journal of Arabic and English Language, 2021)
Purpose - This research describes the model, shape, planning process, and design of the Takhaṣṣuṣ al-Lughah al-'Arabiyah program at Al-Kamal Integrated Islamic Boarding School Blitar. Design/methodology/approach - This research method uses qualitative research, with data in the form of descriptive. Data collection is used employing observation, interviews, and documentation. Findings/result - The results of this study are as follows: 1). Takhaṣṣuṣ al-Lughah al-ʿarabiyah program uses a bottom-up planning model, where the concept of the idea of this activity is created and arranged by the language administrator and then coordinated by the chairman and the board of daily administrators, and approved by the caretaker of the cottage. 2). This form of program planning includes short-term and institutional. 3). The planning process is carried out optimally with clear activity procedures and is easily understood by the students. 4). Learning design is not like formal schools in general, so there is no standard competency and basic competence. The learning strategy uses a jigsaw system to enrich mufradāt or vocabulary by repeating the words that have been learned so that they are quickly memorized. Originality/value - knowing planning management of Takhaṣṣuṣ al-Lughah al-ʿarabiyah Program is very important to be able to measure how good the administration of educational planning in this program. Paper type – Research Paper